Distribution of chlorophyll-a concentration with the catch of julung fish in Ternate Island city - Aisyah Bafagih; Sahriar Hamzah; Umar Tangke (Sekolah Tinggi Ilmu Pertanian Wuna, 2018)
The study was conducted during March-May 2017 in the Coastal Waters of Ternate Island of North Maluku Province with the aim to study the relationship between the concentration of chlorophyll-a and the catch of Hemiramphus sp and its potential fishing area. Using experimental fishing method and non-linear regeneration analysis and GIS analysis. The result of this research shows that oceanographic factor that is chlorophyll-a concentration has significant effect on the catch of julung fish with correlation coefficient value of 0.729, with potential catch area located at three locations ie at coastal of Ngade to Kalumata on location 00o45'00